Pengaruh Terpaan, Efektivitas dan Kualitas Konten terhadap Pemenuhan Kebutuhan Hiburan Pada Youtube Windah Basudara - Arbi Octo Mahendra; Irwandaru Dananjaya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
YouTube Windah Basudara is a YouTube channel that provides entertainment content. This study aims to determine the influence of exposure, effectiveness, and quality of Windah Basudara's YouTube content on fulfilling entertainment needs. This research uses a quantitative approach with a positivist paradigm, where the sample is taken using purposive sampling with a total sample of 400 respondents obtained from calculations using the Slovin formula. The population in this study consists of subscribers of the Windah Basudara YouTube channel. This study employs the Uses and Gratifications theory. Elements of satisfaction include the influence of exposure, effectiveness, quality, and the fulfillment of entertainment needs. The utility is the subscribers of the Windah Basudara YouTube channel. The results of this study indicate that there is an influence of exposure, effectiveness, and quality on the fulfillment of subscribers' entertainment needs. The better the exposure, effectiveness, and quality of the content, the more the entertainment needs are fulfilled. This shows that the results of this study are relevant to the Uses and Gratifications theory, where when an individual obtains satisfaction, a response is formed.